ADAPTASI SUKU ASLI DI DESA JANGKANG ECAMATAN BANTAN KABUPATEN BENGKALIS - Nur’aisyah "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was done in the village of Bengkalis Regency BantanSubdistrictJangkang with Formulation problems (1) How Tribal adaptation for survival amid an increasingly environmentally damaged? (2) how the Government's efforts to improve the welfare of the natives?. The purpose of this research was to find out how Tribal adaptations to survive amid increasingly damaged environment. To find out how the efforts of the Government in the construction of the Original Tribes to improve well-being. This research uses qualitative research methods, the sampling Technique used by researchers is a purposive sample. To get the information this research using the guidelines of the interview. The results of this research can identify the Tribal Adaptation to sustain his life increasingly damaged surroundings they still take the mangrove wood to meet the needs of his life. But there is also the work of the sampingannya catch fish but no one enough to sell only to eat, because it does not have the capital to have large pompong to catch fish and have no capability in other jobs. Bengkalis Regency Government efforts to make the House livable perogram to Tribal communities by not damaging the authenticity of the Original tribes of the environment.Perogram given these social Service is done to improve the welfare of the natives who have homes that are not feasible in the original Tribe to huni. As for the General programs given by the Government to the welfare of society, namely: the home livable, rain water reservoirs, health coverage, Raskim, KUBE (joint ventures), child nutrition school, Indonesian Card smart, Help school clothes bags and prosperous indonesia, cards, family expectations. They are common people can get it all including Original Tribe. Special programs for Native Tribes are the program houses livable. Keywords: Adaptation, Tribal, Welfare